Elevated IP-10 at the Protein and Gene Level Associates With Pulmonary TB - Fisher, Kimone L.; Moodley, Denelle; Rajkumar-Bhugeloo, Kerishka; Baiyegunhi, Omolara O.; Karim, Farina; Ndlovu, Hlumani; Ndung’u, Thumbi; Marakalala, Mohlopheni J. (Frontiers in Cellular and Infection Microbiology, 2022)
There is an urgent need for accurate and sensitive diagnostic tools that can overcome the current challenge to distinguish individuals with latent tuberculosis infection (LTBI) from individuals with active tuberculosis (TB). Recent literature has suggested that a group of cytokines may serve as biomarkers of TB disease progression. Using a multiplex ELISA, we quantified 27 circulatory markers present within the unstimulated plasma of individuals in Durban, South Africa who were healthy (n=20), LTBI (n=13) or had active TB (n=30). RT-qPCR was performed to measure gene expression of the cytokines of interest, using RNA isolated from healthy (n=20), LTBI (n=20) or had active TB (n=30). We found that at the protein level, IL-1RA, IL-6 and IP-10 were significantly more abundant in participants with active TB (p< 0.05) compared to those with LTBI individuals. IP-10 also showed the strongest association with active TB compared to healthy and LTBI at mRNA level. Our data shows that these proteins may serve as biomarkers of TB at both the protein and gene level.